The bear report - Heder, Thyra (Abrams Books for Young Readers, 2015)
Sophie is uninterested in writing a research report on polar bears until a polar bear named Olafur swoops her away to the Arctic, where she learns all about the playful bear's habits and habitat, from glacier mice to Northern Lights.